Switching to recombinant factor IX Fc fusion protein prophylaxis results in fewer infusions, decreased factor IX consumption and lower bleeding rates. (11th September 2014) - Powell, Jerry; Shapiro, Amy; Ragni, Margaret; Negrier, Claude; Windyga, Jerzy; Ozelo, Margareth; Pasi, John; Baker, Ross; Potts, James; Li, Shuanglian; Mei, Baisong; Pierce, Glenn F.; et al.
Summary In the phase 3 B‐LONG [Recombinant Factor IX Fc Fusion Protein (rFIXFc) in Subjects with Haemophilia B] study, rFIXFc dosed every 1–2 weeks was safe and efficacious in previously treated subjects with haemophilia B. To date, there are no evaluations of transitioning from conventional to long‐acting factor IX (FIX) prophylaxis. This post‐hoc analysis of B‐LONG subjects compared prophylaxis with other FIX products and rFIXFc. Pre‐ and on‐study data were analysed to assess dosing regimen, weekly FIX consumption and annualized bleeding rates (ABRs). Population pharmacokinetics models were used to generate FIX activity profiles with rFIXFc and recombinant FIX prophylaxis. Thirty‐nine subjects, previously treated prophylactically, were evaluated. Prior to study, most subjects (69·2%) received twice‐weekly FIX infusions; on study, subjects infused rFIXFc once every 1–2 weeks with c. 30–50% reductions in weekly consumption. On‐study estimated mean ABRs were lower than pre‐study estimated mean ABRs. Models predicted that rFIXFc administered 50 iu/kg weekly and 100 iu/kg every 10 d would maintain steady‐state FIX trough levels ≥1 iu/dl in 95·4% and 89·2% of subjects, respectively. These results indicate that patients receiving rFIXFc prophylaxis can markedly reduce infusion frequency and FIX consumption, have a greater likelihood of maintaining FIX activity >1 iu/dl and experience fewer bleeding episodes compared with prior FIX prophylaxis.